The effect of perceived severity on activity of daily living in post non hemorrhagic stroke patients - Yunia Annisa Al Mujaddidah; Siti Istiqomah; Aisyah Lahdji (South East Asia Nursing Research)
Stroke is a major health problem that can lead to disability and death with a higher incidence of non-hemorrhagic stroke compared to haemorrhagic stroke. Stroke often leaves sequelae that cause the patient's condition is not the same as before with the most common problem in the form of muscle weakness that affects the patient's activity of daily living. Efforts can be made to reduce the impact of stroke by increasing healthy behaviour which can be seen in the health belief model theory, one of which is in the aspect of perceived severity. This study was conducted to determine the effect of perceived severity on the activity of daily living of patients after non-hemorrhagic stroke. The method used was analytical observational with a cross sectional approach with a sample of 80 respondents who met the inclusion criteria at KRMT Wongsonegoro Hospital Semarang using the Consecutive Sampling technique. Data were collected using a questionnaire instrument which was then tested using Spearman rank with the help of computer software. The majority of respondents had a high level of perceived severity at 58 respondents (72.5%) and independent activity of daily living results at 32 respondents (40%). The results of the bivariate test between perceived severity and activity of daily living obtained p value 0.000. There is a significant influence between perceived severity on the activity of daily living of post-stroke non haemorrhagic patients (p value 0.000).